Effect of thickness and halide composition on the resistive switching and photonic synapse properties of methylammonium lead bromide thin films - Choi, Won Chang; Yun, Yeonghun; Lee, Sang Myeong; Kang, Yunmo; Jung, Hyun Suk; Cho, In Sun; Lee, Sangwook (Journal of Alloys and Compounds, 2025)
Recently, photonic synapses based on halide perovskite resistive switching devices have been intensively studied due to their low power consumption, high information processing speed, and the ability to simultaneously receive optical and electrical signals. In this study, the resistive switching behavior and photo-synaptic properties of methylammonium lead bromide (MAPbBr3) thin films were investigated by varying thicknesses and substituting bromine with chlorine. The thickest film (330 nm) exhibits a single step of resistive switching from a high resistance state to a low resistance state (SET), which is attributed to the formation of conductive filaments by the migration of halide vacancies. In contrast, thinner films (100 nm and 210 nm) show two steps of SET where both the halide vacancies and electrode ions (Ag+) are involved in the formation of conductive filaments. Among the films, the 210 nm-thick film exhibited the most effective potentiation by repeated light exposure. When incorporating Cl into the MAPbBr3 film, the resistive switching voltages and the light-induced potentiation was decreased. This was attributed to the smaller ion size of Cl compared to Br, which facilitates ion migration and the formation of vacancy filaments. Short-term potentiation and long-term depression under light pulses were characterized using paired-pulse facilitation and paired-pulse depression.
Keywords: Chlorine substitution; Conductive filaments; Effects of thickness; Film-thickness; Halide perovskites; Lead bromide; Photonic synapse; Property; Resistive switching; Thin-films; Chlorine substitution; Film thickness; Halide perovskites; Photonic synapse; Resistive switching